Microphysiological Systems: automated fabrication via extrusion bioprinting - Prendergast, Margaret Elizabeth; Montoya, Gabriel; Pereira, Taciana; Lewicki, Jakub; Solorzano, Ricky; Atala, Anthony (Microphysiological Systems, 2018)
Microphysiological systems (MPS) offer great potential for improving pre-clinical testing for pharmaceutical treatments and novel therapies. These advanced in vitro models are designed to recapitulate the basic functions of living tissues or organs through dynamic culture and biomimetic microarchitecture. Increasing advancements in MPS design require advanced fabrication methods, such as extrusion bioprinting. Extrusion bioprinting presents the ability to automate fabrication of these systems in a simplified, one-step process, while providing the ability to fabricate complex, reproducible designs that incorporate dynamic culture, 3D microtissues and integrated sensors for analysis into a single system. This work reviews the main components that constitute these systems, current state-of-the-art MPS fabricated via extrusion bioprinting, and future considerations for the development of MPS.